CRITICAL THINKING MODELS AND READING COMPREHENSION INSTRUCTION : A THEORETICAL STUDY - Murwani Ujihanti; Wasitoh Meirani; Nian Masna Evawati (Politeknik Negeri Sriwijaya, 2016)
The main purpose of this writing is to review and how to implement two critical thinking models, namely model to generate critical thinking and critical questions – a linear model. These two critical thinking models can be applied in the reading comprehension instruction, since there relationship between reading comprehension and critical thinking is so close. The specific issues being discussed include schema theory as a rational premise for the connection between reading comprehension and critical thinking, cognitive development processes, critical thinking: its nature and definitions, critical thinking: skills and dispositions, and critical thinking and reading comprehension. The results revealed that: (1) there is well established relationship between reading comprehension and critical thinking, (2) schema theory provides a rational premise for that relation, and (3) there is no consensus regarding the definition of critical thinking which might be interpreted as a lack of an accepted framework for critical thinking.